2015
DOI: 10.1021/tx500468h
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Method for Quantifying Sulfur Mustard Adducts to Blood Proteins by Ultrahigh Pressure Liquid Chromatography–Isotope Dilution Tandem Mass Spectrometry

Abstract: Sulfur mustard binds to reactive cysteine residues, forming a stable sulfur-hydroxyethylthioethyl [S-HETE] adduct that can be used as a long-term biomarker of sulfur mustard exposure in humans. The digestion of sulfur mustard-exposed blood samples with proteinase K following total protein precipitation with acetone produces the tripeptide biomarker [S-HETE]-Cys-Pro-Phe. The adducted tripeptide is purified by solid phase extraction, separated by ultra-high pressure liquid chromatography, and detected by isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
(67 reference statements)
1
22
0
1
Order By: Relevance
“…The results indicated that pH value of enzymatic buffer had significant influence on the yield of adducted tripeptide with variation of over 50 %, and the highest signal response was from pH 8.0 of 20 mM Tris HCl, which had not previously been reported. The investigated digestion reaction at 40, 50, and 60°C showed that temperature was a critical factor, and there were higher signals at 50 and 60°C, which is consistent with that of previous study [17]. Conditions in enzyme concentration (2.00, 4.00, 6.00 mg•mL -1 ) and digestion time (1.0, 2.0, 4.0, 8.0, 12.0 h) were also optimized and investigated.…”
Section: Proteinase K Digestion Of Alb Forming Stable Tripeptide Adductsupporting
confidence: 92%
See 4 more Smart Citations
“…The results indicated that pH value of enzymatic buffer had significant influence on the yield of adducted tripeptide with variation of over 50 %, and the highest signal response was from pH 8.0 of 20 mM Tris HCl, which had not previously been reported. The investigated digestion reaction at 40, 50, and 60°C showed that temperature was a critical factor, and there were higher signals at 50 and 60°C, which is consistent with that of previous study [17]. Conditions in enzyme concentration (2.00, 4.00, 6.00 mg•mL -1 ) and digestion time (1.0, 2.0, 4.0, 8.0, 12.0 h) were also optimized and investigated.…”
Section: Proteinase K Digestion Of Alb Forming Stable Tripeptide Adductsupporting
confidence: 92%
“…However, the level of 4.00 mg•mL -1 enzyme and digestion time ≥4.0 h had relatively high and stable yields of the tripeptide adduct. Obviously, longer digestion time was needed in our study than 1.5 h of the previous study [17], which could be well explained by the fact that the digestion mixture was stirred in the previous study, while it was not stirred during digestion in our study. Interestingly, longer time for digestion (16,24, and 48 h) was also investigated with the result that the yields of the tripeptide adduct were still stable to 48 h, suggesting that proteinase K digestion of ALB can form stable tripeptide adduct.…”
Section: Proteinase K Digestion Of Alb Forming Stable Tripeptide Adductmentioning
confidence: 63%
See 3 more Smart Citations